Oscar Wilde's The Happy Prince: Semiotics Study (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The purpose of this paper is to explore the basics of semiotic analysis in general and the semiotic Theory formulated by the American philosopher Charles Stander Peirce in particular. Thus, after providing a number of definitions for semiotics from the point of view of several scholars and providing a clear representation of Peirce's Theory, the researcher selects a short story by the great Irish writer Oscar Wilde as a sample to apply Peirce's Theory to it.